Utility of transesophageal echocardiography to assess real time left atrial pressure changes and dynamic mitral regurgitation following placement of transseptal multistage venous cannula for systemic venous drainage and indirect left ventricular venting in venoarterial extracorporeal membrane oxygenation. Issue 3 (22nd February 2021) - Meers, Jacob Bradley; Nanda, Navin C.; Watts, Thomas Evan; Prejean, Shane; Hoopes, Charles W.; Lenneman, Andrew; Ahmed, Mustafa I.
Abstract: A patient with heart failure due to nonischemic cardiomyopathy presented as a transfer to our institution following peripheral (femoral) venoarterial (VA) extracorporeal membrane oxygenation (ECMO) placement. With peripheral VA ECMO cannulation, the patient continued to have unstable ventricular tachyarrhythmias. Echocardiography demonstrated left ventricular (LV) dilation and severe mitral regurgitation (MR) with clinical and chest X‐ray evidence of pulmonary edema. To provide venous drainage and simultaneous decompression of the left atrium (LA) and thereby indirect LV venting, a single multistage venous cannula was placed across the inter‐atrial septum (IAS) using the previously described left atrial venoarterial (LA‐VA) ECMO cannulation technique. Two‐ and three‐dimensional (3D) transesophageal echocardiography (TEE) demonstrated utility in guiding cannula placement into the appropriate position and providing real time assessment of ventricular decompression and MR severity. There was subsequent improvement in pulmonary edema. This case is thought to be the first demonstration of real time resolution of pulmonary venous flow reversal in a patient undergoing LA‐VA ECMO cannulation. This demonstration offers important mechanistic insight into some of the potential benefits of such an approach.